Implementation of Restrictions on Defamation Regulations According to the ITE Law - Avrijsto Amandri Achyar; Suartini (PALAR | PAKUAN LAW REVIEW, 2026)
The crime of defamation in the digital space is now specifically regulated in Article 27A of Law Number 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions Law (ITE). Despite this regulatory reformulation, a significant research gap exists regarding the effectiveness of the article's operational boundaries in mitigating legal ambiguity at the judicial level, as prior studies remain dominated by older case analyses that do not represent the latest normative dynamics. This study aims to analyze the limitations of this criminal regulation and its implementation in judges' considerations to maintain a balance between reputation protection and freedom of expression. Using a normative juridical method with a statutory approach, this study finds that the legal limitations of Article 27A rest on cumulative proof of the elements of the offense. The main element of "attacking honor or good name" requires objective proof, often requiring testimony from a linguist to identify defamatory content that damages dignity. Furthermore, the element of "with the intent to make it publicly known" is fulfilled if the content is publicly accessed through an electronic system. The results of the analysis of decisions indicate disparities in sentencing influenced by judges' subjective considerations regarding case background, expert testimony, and aggravating factors such as repeated behavior. In conclusion, the enforcement of Article 27A requires thoroughness in proving specific elements to ensure legal certainty and proportionality of decisions in defamation disputes in electronic media. Keywords : Electronic Information and Transactions; Defamation; Criminal Liability; Cyber Crime.